The Influence of Human Resource Quality on Crew Ship Performance at Bourbon Offshore Asia Pte., Ltd - Purba, Julyana; Siska, Syafni Yelvi (PT Aksara Indo Rajawali, 2025)
This study aims to analyze the influence of Human Resource (HR) quality on crew performance at Bourbon Offshore Asia Pte., Ltd. The primary focus of the research is on how HR quality affects the operational effectiveness of ships, which in turn impacts safety and work efficiency in the maritime environment. This study employs a quantitative method using a questionnaire instrument that has been tested for validity and reliability. The data are analyzed using linear regression to determine the relationship between HR quality and crew performance. The results indicate that the majority of crew members have 0–4 years of work experience, highlighting the need for more effective training strategies to enhance their competencies. In terms of job distribution, 53.75% of the crew consists of deckhands (ABK), who play a crucial role in daily ship operations. The regression test results indicate a positive and significant relationship between HR quality and crew performance, with a correlation coefficient of 0.926. The coefficient of determination (R² = 0.857) indicates that 85.7% of the variation in crew performance is explained by HR quality, while 14.3% is attributed to other factors. Key factors improving crew performance include individual competence, work productivity, and compliance with safety standards. However, aspects such as work initiative and task completion require further attention.